Detection of the intraoperative bile leakage in laparoscopic cholecystectomy using indocyanine green fluorescence imaging: A case report. Issue 3 (March 2023) - Li, Xin-kai; Wang, Piao; Su, Song; Gan, Yu; Yang, Xiao-li; Peng, Fang-yi; Hu, Zhen-hua; Tian, Jie; Fang, Cheng; Li, Bo
Abstract: Herein, we report two cases of successful application of indocyanine green (ICG) fluorescence imaging for detecting intraoperative bile leakage during laparoscopic cholecystectomy (LC). Bile leakage was detected rapidly and accurately using fluorescence guidance. Based on our findings, we recommend using ICG fluorescence imaging during LC because it is effective and feasible for detecting intraoperative bile leakage. Highlights: The first study using ICG fluorescence imaging to detect intraoperative bile leakage during LC. The use of ICG fluorescence imaging technology can rapidly and accurately detect intraoperative bile leakage.